The extreme capsule and aphasia: proof-of-concept of a new way relating structure to neurological symptoms. Issue 2 (14th March 2021) - Martinez Oeckel, Ariane; Rijntjes, Michel; Glauche, Volkmar; Kümmerer, Dorothee; Kaller, Christoph P; Egger, Karl; Weiller, Cornelius
Abstract: We present anatomy-based symptom-lesion mapping to assess the association between lesions of tracts in the extreme capsule and aphasia. The study cohort consisted of 123 patients with acute left-hemispheric stroke without a lesion of language-related cortical areas of the Stanford atlas of functional regions of interest. On templates generated through global fibre tractography, lesions of the extreme capsule and of the arcuate fascicle were quantified and correlated with the occurrence of aphasia ( n   =  18) as defined by the Token Test. More than 15% damage of the slice plane through the extreme capsule was a strong independent predictor of aphasia in stroke patients, odds ratio 16.37, 95% confidence interval: 3.11–86.16, P   <  0.01. In contrast, stroke lesions of >15% in the arcuate fascicle were not associated with aphasia. Our results support the relevance of a ventral pathway in the language network running through the extreme capsule. Abstract : Abbreviated summary Martinez Oeckel et al. report that aphasia after stroke is associated with lesions of the extreme capsule fibres and not with lesions of the arcuate fascicle. They use a new promising method of anatomy-based lesion-symptom mapping, mapping lesions of either tract on the occurrence of aphasia in acute stroke patients. Graphical Abstract: